Effect of pulse width of a 595-nm flashlamp-pumped pulsed dye laser on the treatment response of keloidal and hypertrophic sternotomy scars - Woraphong Manuskiatti (2018)
BACKGROUND: Flashlamp-pumped pulsed dye lasers (PDLs) have successfully treated keloidal and hypertrophic scars. OBJECTIVE: The objective was to investigate the effect of pulse width of a PDL in treating keloidal and hypertrophic scars. METHODS: On each of 19 patients, keloidal or hypertrophic median sternotomy scars were divided into two segments. Both segments on all patients were randomly treated with a 595-nm PDL at a fluence of 7 J/cm 2 and pulse widths of 0.45 and 40 ms to both segments, every 4 weeks for a total of three treatments. Scar volume, height, erythema, and pliability were measured at Weeks 0, 4, 8, and 24. RESULTS: The volume of segments treated with 0.45- and 40-ms pulses decreased significantly after two treatments. Segments treated with a 0.45-ms pulse width showed significantly greater improvement than those treated with 40-ms pulses after three treatments. Elasticity of 0.45-ms segments was significantly higher than those of 40-ms segments, following two treatments. Pulse width had no significant effect in improvement of scar erythema. CONCLUSIONS: A pulse width of 0.45 ms of PDL was more effective in decreasing scar size and improving scar pliability than that of 40 ms. A 595-nm PDL was safe and effective in treatment of hypertrophic scars and keloids in dark-skinned individuals. © 2007 by the American Society for Dermatologic Surgery, Inc.